EFFECTS OF EARLY IDENTIFICATION ON COGNITIVE SKILLS AND ACADEMIC ACHIEVEMENT OF HEARING-IMPAIRED STUDENTS - Abid Masood Khan, Sadia Sultan (JIE, 2024)
Early identification is the process of identifying any developmental delays or impairments in the early years of a child's life and realizing the need of early intervention. The cognitive performance and academic achievements depend on the early identification and on the social/educational background of the family. The purpose of the present study was to explore the effects of early identification on cognitive development and academic achievement of hearing-impaired students. This was a descriptive study and survey method was used to collect the data. Population of the study was hearing impaired students taking their education from government special education institutions Faisalabad Division,Punjab, Pakistan. Sample of the study was N=200 hearing impaired students with mild to moderate degree hearing loss which were selected through purposive sampling technique.